1987
DOI: 10.1037/0022-0663.79.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Peer-model attributes and children's achievement behaviors.

Abstract: Abstract:In two experiments, we investigated how attributed of peer models influenced achievement behaviors among children who had experienced difficulties learning mathematical skills in school. In Experiment 1, children (M = 10.6 years) observed either a same-or opposite-sex peer model demonstrating rapid (mastery model) or gradual (coping model) acquisition of fraction skills. Observing a coping model led to higher self-efficacy, skill, and training performance. In Experiment 2, children (M = 10.9 years) ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
2
12

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(189 citation statements)
references
References 31 publications
(61 reference statements)
6
165
2
12
Order By: Relevance
“…For example, Schunk and colleagues found that perceived self-efficacy for learning correlates positively with students' rate of solution of arithmetic problems (Schunk & Hanson, 1985;Schunk, Hanson, & Cox, 1987). Salomon (1984) has found that self-efficacy is positively related to self-rated mental effort and achievement during students' learning from text material that was perceived as difficult.…”
Section: Role Of Self-efficacy In Academic Motivationmentioning
confidence: 99%
“…For example, Schunk and colleagues found that perceived self-efficacy for learning correlates positively with students' rate of solution of arithmetic problems (Schunk & Hanson, 1985;Schunk, Hanson, & Cox, 1987). Salomon (1984) has found that self-efficacy is positively related to self-rated mental effort and achievement during students' learning from text material that was perceived as difficult.…”
Section: Role Of Self-efficacy In Academic Motivationmentioning
confidence: 99%
“…Schunk and Hanson (1985) found no differential effects of a peer coping or a peer mastery model (both were better than an adult model, which was better than no model), but Schunk et al (1987) showed that coping peer models were more effective than mastery peer models and that children who observed coping peer models judged themselves to be more similar in competence to the models. Braaksma et al (2002) gave learners in two observational learning conditions both good and weak peer models.…”
Section: How Should Examples Be Designed To Optimize Their Effectivenmentioning
confidence: 99%
“…Schunk et al 1987). In an experimental study with 103 undergraduate students, she manipulated type of agent model (coping versus mastery) and interaction type (direct versus vicarious) and found a main effect where the agent as a coping model positively impacted learner motivation, self-efficacy and attitude.…”
Section: Visual Presence Of the Agentmentioning
confidence: 99%